Computer crimes and internal auditor - Chua, Siew Mei (2013)
In recent years, computer crimes are posing a growing and major threat to organisations around the world. This is due mainly to the fact that organisations are relying more on technology and people are also becoming more computer literate. In order to deter people from directly or indirectly committing computer or computer related crimes, the Computer Misuse Act (Chapter 50A) was enacted on 30 August 1993.